Syntactic Study of Transitional Words in English (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
The current study focuses on the concept of transition words, which can be classified as both stylistic and syntactic phenomena. According to Quirk et al. (1985:634), conjuncts have seven roles. One of these roles is a transitory one. The problem with this study is that learners have difficulty reading some texts. This study seeks to evaluate the role of transitional words in perceiving utterances or sentences. It is hypothesized that no English text is free of transitional words. It has been found that English demonstrates more illustration and development of transitional terms by using them in sentences or utterances. The current study is valuable since it gives appropriate background information for those interested in this topic.